Analisis Pengaruh Kesadaran Merek dan Citra Merek Terhadap Minat Pembelian - Dati Putra Nur Akhmad; Mirzam Arqy Ahmadi (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research was used to find out how brand awareness and brand image impact interest in purchasing iPhone products in Indonesia. Brand awareness includes recognition of the product and logo, while brand image involves consumer perceptions regarding product quality and exclusivity. This research uses a quantitative method by distributing questionnaires to 150 respondents who are iPhone users. Data were analyzed using SEM PLS, which showed that both brand awareness and brand image had a positive and significant influence on purchase intention. These results indicate that increasing brand awareness and image can encourage consumers to prefer iPhone over other brands. It is hoped that this research will provide guidance for companies in developing marketing strategies that focus on increasing brand awareness and image to attract consumer interest.